Engineering iron and stone : understanding structural analysis and design methods of the late 19th century - Boothby, Thomas E. (ASCE Press/American Society of Civil Engineers, 2015)
This book presents a comprehensive explanation of the empirical, graphical, and analytical design techniques used during this period in the construction of both large and small buildings and bridges in wood, stone, brick, and iron. Drawing on a career-long fascination with how structural engineers do their work, Author provides specific examples of these analysis and design methods applied to arches, girders, trusses, beams, and columns. The numerous calculations, drawings, and photographs, both historic and contemporary, illustrate the application of these techniques to a wide range of structures. --